NUMBER WHEEL MEDIA: IMPROVING NUMERACY SKILLS AT 'AISYIYAH GUIDANCE CENTER MALAYSIA - Utami, Vivi Audya; Syamsuyurnita, Syamsuyurnita (JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
This research aims to improve the numeracy skills of 1st-grade students at the ‘Aisyiyah Guidance Center Kampung Pandan Malaysia through number wheel media. This research used a Classroom Action Research (CAR) method with a qualitative approach, conducted in two cycles. The research subjects were 15 1st-grade students, consisting of 8 female students and 7 male students. Data collection techniques included observation, interviews, and tests. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection. The research focused on improving numeracy skills within the range of numbers 1-10, specifically in addition and subtraction operations. The results of this research indicated an improvement in students’ numeracy abilities. The average student score in the Pre-Cycle was only 57.33, with a classical completeness of 20%. After Cycle I, using the number wheel media, the average score increased to 64 with a classical completeness of 46%. In Cycle II, the average score reached 88, with a classical completeness of 100%. Number wheel media proved to be effective in enhancing numeracy skills. This media taught mathematical concepts and encouraged students to observe and practice the relationship between addition and subtraction symbols. Teacher and student activities also increased, from 83% and 75% in Cycle I to 91% and 96% in Cycle II. This research concludes that number wheel media can be an innovative strategy to improve elementary school students’ numeracy skills.